(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
The Structure, Electron density and HOMO-LUMO analysis of TTF molecule was carefully evaluated by ab initio (HF) and density functional theory (B3LYP) calculations. The optimized (HF/6-311G** and B3LYP/6-311G**, B3LYP/auf-cc-PVDZ) geometric parameters are in excellent agreement with the similar type experimental data. For both levels of calculation, the low charge accumulation have C\(-\)S and C\(\)N bonds, at the bond critical point, which gives that the bond charges are highly depleted compared with all other bonds in the molecule. Further, AIM theory shows the difference of charge distribution in all bonds. The molecular conductivity (HOMO-LUMO gap) properties are solely related to the ESP of the entire system. The ionization potential gives the very good information of conductivity. These observations give an insight on this kind of super conducting material, which are useful to design navel electronic devices.